Feasibility of Topical Applications of Natural High-Concentration Capsaicinoid Solutions in Patients with Peripheral Neuropathic Pain: A Retrospective Analysis - Fanny Bauchy; Andre Mouraux; Ronald Deumens; Marjolein Leerink; Antonio Ulpiano Trillig; Bernard le Polain de Waroux; Arnaud Steyaert; Quetin-Leclercq Joëlle; Patrice Forget (Pain Research and Management)
Background. Capsaicin, one of several capsaicinoid compounds, is a potent TRPV1 agonist. Topical application at high concentration (high concentration, >1%) induces a reversible disappearance of epidermal free nerve endings and is used to treat peripheral neuropathic pain (PNP). While the benefit of low-concentration capsaicin remains controversial, the 8%-capsaicin patch (Qutenza®, 2010, Astellas, Netherlands) has shown its effectiveness. This patch is, however, costly and natural high-concentration capsaicinoid solutions may represent a cheaper alternative to pure capsaicin. Methods. In this retrospective study, 149 patients were screened, 132 were included with a diagnosis of neuropathic pain, and eighty-four were retained in the final analyses (median age: 57.5 years [IQR25–75: 44.7–67.1], male/female: 30/54) with PNP who were treated with topical applications of natural high-concentration capsaicinoid solutions (total number of applications: 137). Indications were postsurgical PNP (85.7%) and nonsurgical PNP (14.3%) (posttraumatic, HIV-related, postherpetic, and radicular PNP). Objectives. To assess the feasibility of topical applications of natural high-concentration capsaicinoid solutions for the treatment of PNP. Results. The median treated area was 250 cm2 [IQR25–75: 144–531]. The median amount of capsaicinoids was 55.1 mg [IQR25–75: 28.7–76.5] per plaster and the median concentration was 172.3 μg/cm2 [IQR25–75: 127.6–255.2]. Most patients had local adverse effects on the day of treatment, such as mild to moderate burning pain and erythema. 13.6–19.4% of the patients experienced severe pain or erythema. Following treatment, 62.5% of patients reported a lower pain intensity or a smaller pain surface, and 35% reported a sustained pain relief lasting for at least 4 weeks. Conclusion. Analgesic topical treatment with natural high-concentration capsaicinoid is feasible and may represent a low cost alternative to alleviate PNP in clinical practice.